ONASSESSINGSUBJENCTIVEANDGERUNDCOMPLEMENTSIN PERSIANCONTROLCONSTRUCTION: THEPOSITIONOFGERUNDIN PERSIAN - Mahnaz Alikhouei, Bahram Modarresi,Mojtaba Monshizadeh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims at assessing the gerund position in control constructions of Persian. When analyzing control constructions of Farsi, almost all linguists came to agreement that English gerund complement equals to Persian implicit complement. Upon the gerund position in grammar, some linguists believe that there is no verb gerund in today Persian. However, others completely disagree. The point which is worth noting is that, whether agreed with the existence of Persian gerund, there is an inevitable fact: the use of gerund is decreased in today Farsi. Therefore, this study attempts to answer this question that why implicit mode is used instead of gerund in Persian control constructions. To this end, firstly, two important attitudes on gerund position in Farsi will be explained. Then, two implicit and gerund modes will be compared in order to reach existent shared points. Finally, the researcher concludes that plenty of different structural similarities between these two modes in Farsi have resulted in replacing gerund mode with implicit one (at least in control constructions).